Dysbiosis-Associated Polyposis of the Colon—Cap Polyposis - Okamoto, Kazuki; Watanabe, Tomohiro; Komeda, Yoriaki; Okamoto, Ayana; Minaga, Kosuke; Kamata, Ken; Yamao, Kentaro; Takenaka, Mamoru; Hagiwara, Satoru; Sakurai, Toshiharu; Tanaka, Tomonori; Sakamoto, Hiroki; et al. (Frontiers in Immunology, 2018)
Cap polyposis is a rare gastrointestinal disease characterized by multiple inflammatory polyps located between the distal colon and the rectum. Despite the lack of clarity regarding its pathogenesis, mucosal prolapse, chronic inflammatory responses, and Helicobacter pylori infection are considered key contributors to the development of this disease entity. Although it is now generally accepted that dysbiosis of gut microbiota is associated with intestinal and extra-intestinal diseases, alterations of intestinal microbiota have been poorly defined in cap polyposis. Here, we report a patient with Helicobacter pylori-negative cap polyposis who was successfully treated with antibiotics and exhibited dramatic alterations in intestinal microbiota composition after antibiotic treatment. The patient was treated with oral administration of ampicillin and metronidazole and showed regression of cap polyposis 6 months after antibiotic treatment. Fecal microbiota analysis using the next-generation sequencing technology revealed a significant alteration in the intestinal microbiota composition following antibiotic treatment—a marked reduction of Blautia, Dorea, and Sutterella was observed concomitant with a marked increase in Fusobacterium. These data suggest that cap polyposis may originate from dysbiosis and that microbiome-targeted therapy may be useful in this disorder.